2018
DOI: 10.1097/md.0000000000011978
|View full text |Cite
|
Sign up to set email alerts
|

Which neoadjuvant chemotherapy regimen should be recommended for patients with advanced nasopharyngeal carcinoma?

Abstract: Background:The clinical application has widespread disagreement on the different regimens of neoadjuvant chemotherapy (NCT) in the treatment of locoregionally advanced nasopharyngeal carcinoma (NPC). We conducted a network meta-analysis (NMA) to evaluate the efficacy of the different NCT regimens in the treatment of NPC.Methods:A systematic literature search was performed using PubMed, Embase, and Cochran Library. Totally, 31 randomized controlled trials (RCTs) (n = 4062) met study selection criteria and were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Several IC regimens, including TP (docetaxel, cisplatin), FP (cisplatin, fluorouracil), and TFP (docetaxel, cisplatin, fluorouracil), are known to improve the survival of patients with NPC. [ 18 , 19 ] A multicenter randomized phase III trial showed that the efficacy of gemcitabine combined with cisplatin (GP) as IC for recurrent or metastatic NPC was similar to that of TFP, and the incidence of 3 or 4 grade adverse events (AEs) was significantly reduced in GP group. [ 19 ] Moreover, gemcitabine has showed high therapeutic efficacy in various tumor types.…”
Section: Introductionmentioning
confidence: 99%
“…Several IC regimens, including TP (docetaxel, cisplatin), FP (cisplatin, fluorouracil), and TFP (docetaxel, cisplatin, fluorouracil), are known to improve the survival of patients with NPC. [ 18 , 19 ] A multicenter randomized phase III trial showed that the efficacy of gemcitabine combined with cisplatin (GP) as IC for recurrent or metastatic NPC was similar to that of TFP, and the incidence of 3 or 4 grade adverse events (AEs) was significantly reduced in GP group. [ 19 ] Moreover, gemcitabine has showed high therapeutic efficacy in various tumor types.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the other two meta‐analyses revealed the advantages of IC + CCRT over those of CCRT for LANPC, including improvements in OS, progression‐free survival, and DMFS 34,35 . Discrepancies in the survival benefits of IC + CCRT might be related to the use of different chemotherapy drugs 36 . Two meta‐analyses 34,35 conducted after 2015 used new IC regimens (e.g., paclitaxel, carboplatin, and gemcitabine; docetaxel, cisplatin, and 5‐fluorouracil; and cisplatin and gemcitabine), revealing positive results in terms of OS and DMFS that were different from those of the three meta‐analyses 31‐33 published before 2015.…”
Section: Discussionmentioning
confidence: 96%
“…NACT of sufficient intensity can remove tiny distant metastases and reduce metastasis's likelihood (Kong et al 2017;Wang et al 2016). Therefore, the appropriate intensity of NACT can improve the prognosis of radical radiotherapy for NPC, but there is still no consensus regarding the intensity and therapeutic regimen of NACT in LANPC (Yuan et al 2018).…”
Section: Discussionmentioning
confidence: 99%